2018
DOI: 10.1016/j.biortech.2018.03.136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liquid hot water, very dilute acid and alkali treatments for enhancing enzymatic digestibility of hazelnut tree pruning residues

Abstract: The effect of pretreatments on the composition of the hazelnut tree pruning residue (HTPR) and on the digestibility of the cellulose was investigated. The liquid hot water (LHW) and the very dilute acid (VDA) treatments were effective in solubilizing hemicellulose. The cellulose conversion increased up to around 60% (corresponding to 32-36 g/L glucose) with decreasing hemicellulose concentration in the pretreated HTPR. The alkali treatment provided partial delignification, however, the glucose production was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…It can be observed that at temperatures of 190°C and 220°C hemicellulose was completely solubilized, disappearing from the solid phase. Sabanci and Buyukkileci (2018) found hemicellulose content reduction on the solid fraction with the increment of temperature and time of liquid hot water pretreatment. They also reported almost complete solubilization of hemicellulose at 210°C.…”
Section: Effect Of Hydrothermal Pretreatment On the Solid Phasementioning
confidence: 88%
“…It can be observed that at temperatures of 190°C and 220°C hemicellulose was completely solubilized, disappearing from the solid phase. Sabanci and Buyukkileci (2018) found hemicellulose content reduction on the solid fraction with the increment of temperature and time of liquid hot water pretreatment. They also reported almost complete solubilization of hemicellulose at 210°C.…”
Section: Effect Of Hydrothermal Pretreatment On the Solid Phasementioning
confidence: 88%
“…Moreover, the ALP samples obtained from relatively severe conditions (1.0%~1.2% NaOH) indicated lower lignin contents compared to those observed in AP and FP (Table 1). Effective lignin removal has also been observed in previous alkaline pretreatments of various biomass wastes [6,13,16].…”
Section: Solid Yields and Compositional Changesmentioning
confidence: 75%
“…The bioconversion process is still constrained due to the recalcitrance of these energy crops. Different pretreatment strategies such as pretreatments using acid, alkaline or hot water, explosion pretreatments with steam or ammonia, and biological pretreatment have been reported for reducing the recalcitrance of lignocellulosic biomass wastes, and hence, enhancing the digestibility of these biomass wastes [12][13][14][15][16][17][18]. Chemical pretreatment has been extensively investigated, from lab-scale studies to large-scale ethanol fermentation applications, especially those using low lignin biomass (e.g., agricultural wastes) as substrates [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations